An Analysis of Speech Acts Performed by A Fitness Influencer, Kayla Itsines, in Her Instagram Captions - Handayani, Widi; Yulina, Christina Atika (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2024)
This study seeks out the speech acts in Kayla Itsines’ Instagram captions. The captions written in the last week of January 2020 were selected as the data. There were 20 captions which consisted of 209 sentences. The results present that representative is the most frequent classification in this study. It only has one type which is claiming. It proves that in her captions, Kayla uses phatic expressions to communicate to her followers since she considers her platform as a community that shares the same interests. Hence, she can express her thoughts or feelings without having to provide the scientific evidence. Further, directive consists of 3 areas in this study; ordering, suggesting, and thanking. Ordering and suggesting have the same occurrence which is 39.75%. It presents that being a fitness influencer means being a role model. Hence, she urges her followers to make suggestions to achieve their goals. Lastly, expressive is used to express liking, congratulating, and thanking. Liking is the highest with 50% total occurrence. It aims to display her excitement towards her followers’ achievement since the goal of an influencer is to influence people to reach their goals.